FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA - Diva Puspa Anggraini; Magdalena Nany (LPPM UNISDA, 2026)
Long audit delays will increase uncertainty and reduce investor and stakeholder confidence in the company's financial condition. This research was conducted to obtain empirical evidence on the influence of capital structure, profitability, company size and reputation of public accounting firms on the timeliness of financial reporting. A total of 192 data on manufacturing companies listed on the IDX in 2022 were analyzed by logistics regression analysis. Capital structure has a significant effect on the timeliness of financial reporting. Meanwhile, profitability, company size and reputation of public accounting firms partially do not have a significant effect on the timeliness of financial reporting